Legality of Testament Cancellation Law and Property Ownership According to Fiqh Al-Syafi’iyyah - Karimuddin; Khairun Asyura; Syamsul Bahri; Syarkawi; Nurul Husna; Fathiatul Ghina (Britain International for Academic Research (BIAR) Publisher, 2019)
Any person who has sufficient assets may inherit a portion of the assets as long as it does not harm the heirs and people who are forced to intend or will not intentionally in their will, the will is invalid. The person who has the will must fulfill the requirements, including adults, sensible, independent and of his own will. So it is not a will made by a minor child and a crazy person. In other cases when the testament inherits the estate and then he cancels the will, or the will inherits more than a third of the total assets but the heir cancels the will, then there will be a problem regarding the legality of the will and the status of ownership of the estate after the cancellation of the will. Based on these problems, a study is made to find a legal clarity that could be a reference for every policy maker. The results of the study and research can be concluded, al-Syafi'iyyah states that a will is only valid within a third of the inheritance as long as there is no permission from the heirs to testate to more than one third of the assets. exceeds the said level. A will also becomes nullified if a person who has a will cancels his will or inherited property no longer belongs to someone who has a will. Ownership of a will after the will is canceled depends on the reason and the person who cancels it. If the cancellation is carried out by the willor then the property is returned to the will of the testator, but if the cancellation of the will is due to a will that exceeds one third of the assets then the will is the right of the heir.